2010
DOI: 10.1016/j.metabol.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous red blood cell membrane fatty acids and sudden cardiac arrest

Abstract: Little is known of the associations of endogenous fatty acids with sudden cardiac arrest (SCA). We investigated the associations of SCA with red blood cell membrane fatty acids that are end products of de novo fatty acid synthesis: myristic acid (14:0), palmitic acid (16:0), palmitoleic acid (16:1 n7), vaccenic acid (18:1 n7), stearic acid (18:0), oleic acid (18:1 n9) and a related fatty acid cis-7 hexadecenoic acid (16:1 n9). We used data from a population-based case-control study, where cases, aged 25-74 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
0
33
1
1
Order By: Relevance
“…Very little information is available on 16:1n-9. A PubMed search on 16:1n-9 returns only epidemiological papers where the fatty acid is merely listed as a minor constituent of certain tissues, with no regard for possible biological or biochemical implications (Zong et al, 2013;Wu et al, 2011;Ma et al, 2015;Lemaitre et al, 2010;Dai et al, 2015). Also, this fatty acid is barely mentioned, if at all, in the specialized lipid websites Cyberlipid Center (http://www.cyberlipid.org/), The Lipid Library (http://lipidlibrary.aocs.org/), and The Lipid Home (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Very little information is available on 16:1n-9. A PubMed search on 16:1n-9 returns only epidemiological papers where the fatty acid is merely listed as a minor constituent of certain tissues, with no regard for possible biological or biochemical implications (Zong et al, 2013;Wu et al, 2011;Ma et al, 2015;Lemaitre et al, 2010;Dai et al, 2015). Also, this fatty acid is barely mentioned, if at all, in the specialized lipid websites Cyberlipid Center (http://www.cyberlipid.org/), The Lipid Library (http://lipidlibrary.aocs.org/), and The Lipid Home (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in both erythrocyte membranes and whole blood, higher levels of the long-chain fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are associated with lower risk [4, 5], and higher levels of the trans -fatty acids are associated with higher risk [6, 7, 8]. In addition, we reported that fatty acid biomarkers of de novo fatty acid synthesis, such as palmitic acid, are associated with higher risk of SCA [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Factor loading was used as a measure of contribution of each FA to each pattern. We named each pattern based on the major contributing FA, taking into account known dietary sources and the FA metabolism of various individual FAs, including trans, omega-3 (n23), dairy products, and DNLrelated FAs (1,7,9,(22)(23)(24)(25)(26)(27). In addition, we examined the variability of each individual FA explained by the FA patterns.…”
Section: Derivation Of Fatty Acid Patternsmentioning
confidence: 99%
“…Several individual fatty acid (FA) 4 biomarkers in tissues and blood, eg, biomarkers of PUFAs, trans FAs, or de novo lipogenesis (DNL), have been associated with the risk of cardiovascular disease (CVD) (1)(2)(3)(4)(5)(6)(7)(8)(9). Although these studies have contributed substantially to knowledge on etiologic roles of FAs, nearly all such studies have focused on selected individual FAs.…”
Section: Introductionmentioning
confidence: 99%